ABDIRAUF FITRAT VIEWS ON SPIRITUALITY IN "FAMILY" - Mustafayev J.Sh.; Yunusov Xumoyun Bunyod o‘g‘li (Лучшие интеллектуальные исследования, 2024)
Abstract: "Family" by Abdirauf Fitrat, a writer and philosopher who played an important role in the development of Uzbek literature and spirituality, has deep thoughts about family relations and spiritual values ​​in society. We will discuss what it describes and its importance in modern society.